2016
DOI: 10.1016/j.semcdb.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of X-chromosome inactivation

Abstract: With the emergence of sex--determination by sex chromosomes, which differ in composition and number between males and females, appeared the need to equalize X--chromosomal gene dosage between the sexes. Mammals have devised the strategy of X--chromosome inactivation (XCI), in which one of the two X--chromosomes is rendered transcriptionally silent in females. In the mouse, the best--studied model organism with respect to XCI, this inactivation process occurs in different forms, imprinted and random, interspers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 167 publications
0
37
0
Order By: Relevance
“…In the mouse, imprinted silencing of the paternal X chromosome (Xp) is initiated at the 4to 8-cell stage, after the zygotic genome is activated (Borensztein et al, 2017b;Deng et al, 2014;Mak et al, 2004;Okamoto et al, 2004). While Xp silencing continues in the extraembryonic lineages, Xp is reactivated in the EPI, followed by random X-inactivation (XCI) after implantation (Payer, 2016). Recently, X chromosome reactivation (XCR) during pregastrula development has been ascertained by showing the contrasting level of X chromosome expression between male and female cells (Mohammed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, imprinted silencing of the paternal X chromosome (Xp) is initiated at the 4to 8-cell stage, after the zygotic genome is activated (Borensztein et al, 2017b;Deng et al, 2014;Mak et al, 2004;Okamoto et al, 2004). While Xp silencing continues in the extraembryonic lineages, Xp is reactivated in the EPI, followed by random X-inactivation (XCI) after implantation (Payer, 2016). Recently, X chromosome reactivation (XCR) during pregastrula development has been ascertained by showing the contrasting level of X chromosome expression between male and female cells (Mohammed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This latter expression pattern has been termed random monoallelic expression, and certainly, genes with such an expression profile exist: most X-linked genes are expressed only from one X chromosome due to random X-chromosome inactivation (X. Galupa and Heard 2015;Payer 2016) , and a similar pattern has also been shown for some autosomal genes, such as olfactory receptors or antigen receptors (Monahan and Lomvardas 2015;Brady, Steinel, and Bassing 2010; . Understanding random monoallelic expression is of particular interest given that quantitative cell-to-cell differences or spatial heterogeneity in allele-specific gene expression have the potential to modify phenotypic outcome if the two alleles harbor different functional variants, as has been described for both X-linked (eg.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to embryonic lineage cells, extra-embryonic cells (i.e., TE cells) maintain the silenced paternal X chromosome throughout embryogenesis. Meanwhile, XCR can be induced during reprogramming of differentiated cells toward pluripotency by nuclear transfer, cell fusion, or ectopic expression of reprogramming factors (for a review, see Pasque and Plath, 2015; Payer, 2016; Vallot et al, 2016). Recently, it was shown that during the early period of reprogramming in hybrid cells between human fibroblasts and mouse embryonic stem cells, human nuclei undergo a loss of XIST and XCI-associated histone marks from the inactive X chromosome to accomplish XCR, although some regions on the X chromosome are refractory to reprogramming (Cantone et al, 2016).…”
Section: Introductionmentioning
confidence: 99%